Sensitivity Analysis of the Diabetic Population Model with Lifestyle Transmission - Chakravarty, Koyel; Das, Sukanya; Guin, Lakshmi Narayan (Journal of Applied Nonlinear Dynamics, 2026)
The present investigation delves into the intricate dynamics of diabetic population, accounting for genetic, hereditary, social, environmental, and lifestyle determinants in the progression from pre-diabetes to diabetes. The model encompasses comorbidities, articulated through a suite of six nonlinear differential equations. Employing numerical methodologies alongside comprehensive stability and sensitivity analyses, it unveils nuanced insights into both biological and social interactions. Theoretical discoveries are vividly illustrated, and the model’s credibility is attested through empirical validation. Conclusions drawn from the findings underscore pivotal parameters, endowing invaluable perspectives on the dynamical system in concert with stability elucidations.